POSISI ILMU KEDOKTERAN DAN ILMU USHULUDDIN DALAM ILMU ISLAM - Danusiri Danusiri (At-Taqaddum, 2015)
As a lecturer, my job is to teach and to administer course of Islamic philosophy. However, the dynamics of the profession had once required me to serve as a lecturer in public colleges. In this institution, I teach Islamic subjects that are integrated with core content of every study program such as midwifery, nursing, nutrition, health analysts, public health, mathematics, statistics, and medicine. Through deep reflection I discovered the concept of 'basic philosophy of iqra', a term borrowed from Quraish Shihab, that derived from QS.Al-"Alaq :1-5.The concept was implemented through the activities of reading both qur’anic verses (quraniyyah) and kauniyyah verses, as the interpretation of the phrase mâ khalaqa. The results of reading can be in the form of something, or a concept or variable(s). If there is a basic relationship between two or more things, between two or more concepts, between two or more variables, then the theory exists. A set of theories that is cognate in the sense of similarity within “the body of knowledge" will bear a science. In principle there is only one science and is derived from Allah in His capacity as al-'Alîm and is taught to man,' allamal insanâna mâ lam ya'lam '. Furthermore, the science will develop in line with the human activities due to continued reading activities which can be sequenced further in the conceptualization, theorization, and saintification. Therefore the science is growing and growing into several branches and continues to cross the borders. At this level, the figure of a science is much more specific. Ushuluddin science seems to be unrelated to medical science, but they actually have the same root i.e., the genealogical structure, namely al-'Alîm. and its implication is that the dichotomy of religion versus general science is really just a myth.